Desenvolvimento de metodologia de simulação para conformidade em compatibilidade eletromagnética para projetos eletrônicos - Comin, Rodrigo (Universidade do Vale do Rio dos Sinos, 2017)
The national automotive division, more precisely in the bus manufacturing segment, efforts are being deposited to improve the manufacturing quality of its vehicles in order to meet the requirements of the internal and external market through electronic projects based on international standards. Furthermore, the electromagnetic compatibility standards stand out because they have a major importance ensuring that electronic devices are able to provide safety to its users, without interfering or being interfered by other devices. The objective of this research is to develop a methodology to design electronic devices which must meet the standards requirements of electromagnetic compatibility. This goal is achieved through the study of radiated and conducted emissions techniques, and using computational tools for simulation of printed circuit boards. From this study it will be possible to reduce costs with laboratory tests, reduce the time required for development, and provide products to the customers in an efficient way. The use of appropriated techniques and good practices during the designs process are the proper way to meet standards and requirements. However, with the evolution of technology and addition of more electronic circuits in smaller areas requires to acquire more knowledge and go deeper in this study. Thus, it is necessary to understand in details the common mode and differential emissions technics, develop simulations which can provide a preview of what the laboratory tests may result, and propose changes in the mechanic and electronic project design in order to meet the limits of the requirements determined in the standards.
Keywords: EMC; EMI; ANSYS; SIwave; Simulação; Modelamento de circuito eletrônicos; CISPR25; EMC; EMI; ANSYS; SIwave; Simulation; Eletronic circuit modeling; CISPR25; ACCNPQ::Engenharias::Engenharia Elétrica